Water content of delivered gases during Helmet Continuous Positive Airway Pressure in healthy subjects: Humidification during Helmet CPAP - Lucchini, Alberto; Bambi, Stefano; Elli, Stefano; Bruno, Martina; Dallari, Roberto; Puccio, Pamela; Villa, Silvia; Rona, Roberto; Fumagalli, Roberto; Bellani, Giacomo; Foti, Giuseppe (Acta Biomedica Atenei Parmensis, 2019)
Introduction: During Continuous Positive Pressure Ventilation delivered through helmet, the patient inhales high flows of gas without adequate conditioning. However, the need to humidify the inspired gas during Helmet-CPAP, has not been sufficiently explored. Methods: Experimental design study. Six healthy individuals underwent High Flow Helmet CPAP with different gas flows (60 and 80 L/min) and FiO2 (0.35, 0.5, 0.7 and 1) generated by a Venturi system, with and without active humidification. The active humidifier setting was 26 ° at the humidification chamber and 28 ° at the helmet gas inlet. At each setting, measurements about temperature and relative humidity inside helmet were taken. Comfort level at each setting was evaluated using a visual analog scale rated from 0 to 10. Results: Without heated humidification, the mean value of absolute humidity in the eight combinations investigated was 5.9±2.1 mg H2O/L, with a mean temperature of 25.8±0.9°. With heated humidification mean absolute humidity was 15.0±3.5 mg H2O/L with mean temperature of 29.0±0.1°. The median comfort scale value was 6 (IQR: 5.25-6.75) during the phase without humidification vs 8 (7.25-8.0 - P<0.01) when active humidification was applied. Conclusions: In healthy subjects undergoing High Flow Helmet CPAP, heated humidifiers with heated wires tubes are necessary to avoid the under-humidification inside the helmet. To obtain patient’s comfort and airways mucosal humidification during continuous Helmet CPAP, the most desirable conditions are reached by heated humidifiers with a humidifying chamber temperature settled between 26-28°C.